Auctioning Process Innovations when Losers' Bids Determine Royalty Rates - Cuihong Fan; Byoung Heon Jun; Elmar G. Wolfstetter (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2009)
We consider a licensing mechanism for process innovations that combines a license auction with royalty contracts to those who lose the auction. Firms' bids are dual signals of their cost reductions: the winning bid signals the own cost reduction to rival oligopolists, whereas the losing bid influences the beliefs of the innovator who uses that information to set the royalty rate. We derive conditions for existence of a separating equilibrium, explain why a sufficiently high reserve price is essential for such an equilibrium, and show that the innovator generally benefits from the proposed mechanism.
urn:nbn:de:bvb:19-epub-13263-0
Keywords: D21; D43; D44; D45; 330; Patents; licensing; auctions; royalty; innovation; R&D; mechanism design; Innovation; Lizenz; Auktionstheorie; Nutzungsentgelt; Industrieforschung; Mechanismus-Design-Theorie; Theorie